A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Multi-technique NMR analysis of liquid CO2 hydrate growth and pore structure evolution in sediments - Yu-Hao Bu; Yi-Fei Sun; Xiao-Cun Ma; Ling-Ban Wang; Zhen-Bin Xu; Yong-Yi Zhai; Jin-Rong Zhong; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Three undescribed terpenoids from the aerial parts of Alstonia scholaris - Bing-ru Liu; Chun-xiang Xu; Dan Liu; Yue Feng; Rong-tao Li; Jin-dong Zhong (Phytochemistry Letters, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

A multi-task deep attention network for simultaneous rapid quantification of sucrose, glucose, and fructose contents in pumpkin using FT-NIR spectroscopy - Yingchao Xu; Jiayu Luo; Shudan Xue; Huihui Han; Wenlong Luo; Wenjun Liu; Qingmin Jin; Huijing Lin; Baoling Chen; Yingyin Lin; Rong Zhang; Yujuan Zhong (Food Chemistry, 2025)

Achieving high-concentration lignocellulosic sugars by using the Trichoderma reesei strain with high β-glucosidase activity for inducer synthesis and cellulase production - Kehang Li; Rong Li; Jiaxin Zhang; Hong Liu; Zhaoxian Xu; Mingjie Jin; Fengwu Bai; Yaohua Zhong (Chemical Engineering Journal, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Methane emissions from fossil fuel extraction and embodied in fossil fuel trade in China - Yi Jin; Xiaoyang Zhong; Rong Yuan; Cuiyang Feng; Xu Tang (Journal of Cleaner Production, 2025)

Kinetics and morphology study of hydrate formation from CO2-H2O emulsion in glass beads - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Dan Rao; Yu Liu; De-Jun Xuan; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Isolation and genomic characterization of multi-drug resistant Morganella morganii strain from Chinese Soft-Shell Turtle Pelodiscus sinensis - Rong-Hua Wang; Meng-Lu Yan; Qing Tan; Jin-Long Wang; Yu-Shuang Luo; Zhong-Yuan Chen (Aquaculture, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

An enhanced model for obtaining at-sensor brightness temperature for UAVs incorporating meteorological features and its application in urban thermal environment - Rong Jin; Lihua Zhao; Peng Ren; Haitang Wu; Xue Zhong; Mingyi Gao; Zichuan Nie (Sustainable Cities and Society, 2025)

Sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Min Tan; Li-Zhong Wang; Jun-Jie Hao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2025)

A new approach to high conversion CO2 hydrate sequestration by CO2/water emulsion injection into marine sediments - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Liang-Liang Ren; Ming Wang; Dan Rao; Yong-Quan Liu; Yi-Bo Hao; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

Quantitative evaluation of hydrate-based CO2 storage in unsealed marine sediments: Viewpoint from the driving force of hydrate formation and CO2-water contact ability - Hong-Nan Chen; Yi-Fei Sun; Wei-Xin Pang; Ming-Long Wang; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Bo-Jian Cao; Dan Rao; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2024)

Biodegradable MAM-based amphiphilic block copolymers: Toward efficient and eco-friendly kinetic inhibitors for methane hydrate formation - Li Wan; Xiang-Long Ding; Ai-Xiang Liu; Hao Cui; Jin-Rong Zhong; Yi-Min Dai (Chemical Engineering Journal, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Effect of humic acid on visible light photocatalytic inactivation of bacteriophage f2 with electrospinning Cu-TiO2 nanofibers: insight into the mechanisms - Rong Cheng; Jin-cheng Xia; Liang-jie Shen; Zhi-peng Shen; Lei Shi; Xiang Zheng; Jian-zhong Zheng (Environmental Science and Pollution Research, 2024)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Differential Diagnosis of DCIS and Fibroadenoma Based on Ultrasound Images: a Difference-Based Self-Supervised Approach - Jin Yin; Jia-Jun Qiu; Jing-Yan Liu; Yi-Yue Li; Qi-Cheng Lao; Xiao-Rong Zhong; Mengling Feng; Hao Du; Shao-Liang Peng; Yu-Lan Peng (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Effects of vegetation type differences induced by human disturbance on the nutrition strategy and gut microbiota of Siberian roe deer - Zi‐ao Yuan; Lin‐qiang Zhong; Hai‐rong Du; Jia‐nan Feng; Xin‐xin Liu; Hong‐yi Yuan; Jin‐hao Guo; Peng Liu; Ming‐hai Zhang (Molecular Ecology, 2023)
The Siberian roe deer ( Capreolus pygargus ) is a widely distributed ungulate in northeast China. Due to a series of human disturbance activities such as large‐scale forest cutting, deforestation and reclamation, road construction in the past, the appearance and internal structure of forest vegetation in the habitat of Siberian roe have changed significantly. At the same time, Siberian roe population had a series of ecological adaptation responses in the face of such habitat changes. Therefore, two typical vegetation types with differences were selected in the Muling Forest, China. We used nutritional ecology and microbial metagenomic analysis techniques to compare the nutritional selection strategy and the structure and functional characteristics of faecal microbiota of Siberian roe groups in two vegetation types. The results showed that the α diversity of dietary and gut microbes of deer in Natural Forest was higher than that in Plantation Forest. However, the gut microbes of the Plantation Forest group contained more unique enzymes in the functional pathways of carbon metabolism and biosynthesis of amino acids. This study suggests that habitat type is associated with plant community composition, and contributes to changes in the intake proportions of major macronutrients by altering the availability, quality, and composition of certain edible plants. Feeding behaviour may be an important regulatory factor of gut microbiota structure and function of deer. The metabolic function of gut microbiota to different nutrients may affect the microbial community structure. Therefore, our results suggest that the gut microbes of Siberian roe may have coevolved with their diets, and reflect the adaptability of deer populations to environmental changes (e.g., vegetation type). Our study provides new insights into how spatial heterogeneity affects nutrition and microecosystems by describing the interactions among the environment, diet, and symbiotic gut microbes in wild ungulates.

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

An approach to the high efficient exploitation of nature gas hydrate and carbon sequestration via injecting CO2/H2 gas mixture with varying composition - Bo-Jian Cao; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Ming-Long Wang; Meng-Ya Niu; Jing-Yu Kan; Chang-Yu Sun; Dao-Yi Chen; Guang-Jin Chen (Chemical Engineering Journal, 2023)

Complex impacts of hydraulic fracturing return fluids on soil microbial community respiration, structure and functional potentials - Cheng Zhong; Camilla L. Nesbø; Konstantin von Gunten; Yifeng Zhang; Xiaoqing Shao; Rong Jin; Kurt O. Konhauser; Greg G. Goss; Jonathan W. Martin; Yuhe He; Pei‐Yuan Qian; Brian D. Lanoil; et al. (Environmental Microbiology, 2022)
Summary The consequences of soils exposed to hydraulic fracturing (HF) return fluid, often collectively termed flowback and produced water (FPW), are poorly understood, even though soils are a common receptor of FPW spills. Here, we investigate the impacts on soil microbiota exposed to FPW collected from the Montney Formation of western Canada. We measured soil respiration, microbial community structure and functional potentials under FPW exposure across a range of concentrations, exposure time and soil types (luvisol and chernozem). We find that soil type governs microbial community response upon FPW exposure. Within each soil, FPW exposure led to reduced biotic soil respiration, and shifted microbial community structure and functional potentials. We detect substantially higher species richness and more unique functional genes in FPW‐exposed soils than in FPW‐unexposed soils, with metagenome‐assembled genomes (e.g. Marinobacter persicus ) from luvisol soil exposed to concentrated FPW being most similar to genomes from HF/FPW sites. Our data demonstrate the complex impacts of microbial communities following FPW exposure and highlight the site‐specific effects in evaluation of spills and agricultural reuse of FPW on the normal soil functions.

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Soil nutrients in relation to vertical roots distribution in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Jin-ming Hu; Yu-hai Bao; Fei Wang; Xiu-bin He (Journal of Mountain Science, 2018)

Effects of potassium deficiency on root morphology, ultrastructure and antioxidant enzyme system in sweet potato (Ipomoea batatas [L.] Lam.) during early growth - Ming Liu; Ai-Jun Zhang; Xiao-Guang Chen; Rong Jin; Hong-Min Li; Zhong-Hou Tang (Acta Physiologiae Plantarum, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

A new flavonoid glycoside from Elsholtzia bodinieri - Jin-Dong Zhong; Yue Feng; Hong-Mei Li; Xue-Shan Xia; Rong-Tao Li (Natural Product Research, 2016)

ROCK-I Derived Bi-functional Peptides with Antibacterial Infection Activity - Zhang-Shuan Yao; Shu-Peng Han; Rong-Zhong Jin (International Journal of Peptide Research and Therapeutics, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Heavy metals in wild marine fish from South China Sea: levels, tissue- and species-specific accumulation and potential risk to humans - Jin-Ling Liu; Xiang-Rong Xu; Zhen-Hua Ding; Jia-Xi Peng; Ming-Hua Jin; You-Shao Wang; Yi-Guo Hong; Wei-Zhong Yue (Ecotoxicology, 2015)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Benfotiamine prevents increased β-amyloid production in HEK cells induced by high glucose - Xiao-Jing Sun; Lei Zhao; Na Zhao; Xiao-Li Pan; Guo-Qiang Fei; Li-Rong Jin; Chun-Jiu Zhong (Neuroscience Bulletin, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Numerical simulation of multiphase flows of CO2 storage in saline aquifers in Daqingzijing oilfield, China - Duo X. Yang; Rong S. Zeng; Y. Zhang; Zhong Q. Wang; S. Wang; C. Jin (Clean Technologies and Environmental Policy, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Maternal inheritance of plastids and mitochondria in Cycas L. (Cycadaceae) - Zhi-Rong Zhong; Nan Li; Dan Qian; Jian-Hua Jin; Tao Chen (Molecular Genetics and Genomics, 2011)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Genetic Polymorphisms of the CACNA2D1 Gene and Their Association with Carcass and Meat Quality Traits in Cattle - Guan-Yu Hou; Zheng-Rong Yuan; Xue Gao; Jun-Ya Li; Hui-Jiang Gao; Jin-Bao Chen; Shang-Zhong Xu (Biochemical Genetics, 2010)

Chemometrics-based approach to modeling quantitative composition-activity relationships for Radix Tinosporae - Shi-Kai Yan; Zhong-Ying Lin; Wei-Xing Dai; Qi-Rong Shi; Xiao-Hua Liu; Hui-Zi Jin; Wei-Dong Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

An insulinoma with clinical and electroencephalographic features resembling complex partial seizures - Shuang Wang; Hai-tao Hu; Shu-qun Wen; Zhong-jin Wang; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2008)

Increased expression of hLRH-1 in human gastric cancer and its implication in tumorigenesis - Shui-Liang Wang; De-Zhu Zheng; Feng-Hua Lan; Xiao-Jun Deng; Jian Zeng; Cheng-Jin Li; Rong Wang; Zhong-Yong Zhu (Molecular and Cellular Biochemistry, 2008)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Genetic Conservation of Hemagglutinin Gene of H9 Influenza Virus in Chicken Population in Mainland China - Jin-Hua liu; Katsunori Okazaki; Aaron Mweene; Wei-Min Shi; Qing-Min Wu; Jing-Liang Su; Guo-Zhong Zhang; Gui-Rong Bai; Hiroshi Kida (Virus Genes, 2004)

Expression and import of an active cellulase from a thermophilic bacterium into the chloroplast both in vitro and in vivo - Rongguan Jin; Stefan Richter; Rong Zhong; Gayle K. Lamppa (Plant Molecular Biology, 2003)

Cloning, expression and genomic structure of a novel human GNB2L1 gene, which encodes a receptor of activated protein kinase C (RACK)* - Shu Wang; Jin-zhong Chen; Zhen Zhang; Shaohua Gu; Chaoneng Ji; Rong Tang; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)

Mapping of leaf and neck blast resistance genes with resistance gene analog, RAPD and RFLP in rice - Jie-Yun Zhuang; Wen-Bin Ma; Jian-Li Wu; Rong-Yao Chai; Jun Lu; Ye-Yang Fan; Min-Zhong Jin; Hei Leung; Kang-Le Zheng (Euphytica, 2002)

Cloning and identification of a cDNA that encodes a novel human protein with thrombospondin type I repeat domain, hPWTSR - Jin-Zhong Chen; Shu Wang; Rong Tang; Quan-Sheng Yang; Enpeng Zhao; Yaoqiong Chao; Kang Ying; Yi Xie; Yu-Min Mao (Molecular Biology Reports, 2002)